COMPLETE PARENTS DAN KEBERLANJUTAN SEKOLAH PENDUDUK USIA 7-18 TAHUN DI INDONESIA - Riska Eka Agustina (JURNAL LITBANG KOTA PEKALONGAN, 2022)
The presence of complete parents plays the primary role in supporting the sustainability of schooling for students aged 7-18. This study aims to analyze the characteristics of the students aged 7-18 according to the existence of parents (complete parents and incomplete parents) and the sustainability of their schooling, and the effect of complete parents on the sustainability of schooling for students aged 7-18. This research uses data from Susenas for March 2019 on a national scale. The study used a descriptive analysis and a chi-square test. The results show that the characteristics of the students aged 7-18 who are still in school are dominated by residents with complete parents, in the aged group 7-12 years, females, non-disabled, have received the Smart Indonesia Program for the last year, live in the urban areas, have several household members less than the same as five people, come from a household whose the household head is highly educated and works in the non-agricultural sector. The chi-square test result shows that the sustainability of schooling in the population aged 7-18 years has a statistically significant relationship with the status of the presence of parents. Efforts to strengthen family resilience need to increase the role of both parents in supporting children's education.  Keywords: 7-18 years; schooling sustainability; complete parents